Artificial Intelligence and Credit Scoring: The European Court of Justice Takes Action (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Recently, the European Court of Justice ruled on the subject of credit scoring calculations with techniques based upon artificial intelligence, which constitute cases of great interest, because the judge finally turned his attention to companies such as Schufa and B&D. This kind of dispute, between evaluated parties and scoring companies, will be probably destined to grow over the next few years and will almost certainly lead to questioning the rights of individuals with reference to the breadth of the right to information on the logic of the algorithm involved to achieve the final result.
Keywords: artificial intelligence; credit scoring; proper to information; explainability; algorithm